Peningkatan Daya Berpikir Kritis Dan Kemampuan Literasi Mahasiswa Terhadap Kondisi Lingkungan Kota Bontang Sebagai Kota Industri Melalui Perkuliahan Bahasa Indonesia - Irianto (Manajemen Pendidikan Program Doktor, 2026)
The development of Bontang as one of Indonesia’s industrial cities has had a significant impact on social, economic and environmental aspects. These conditions require students, as the intellectual generation, to possess critical thinking skills and good literacy in understanding, analysing, and providing solutions to various environmental problems arising from industrial activities. Indonesian language courses play a strategic role in developing these skills through critical reading, text analysis, scientific discussions, and the writing of academic papers based on local environmental issues. This study aims to analyse the improvement in students’ critical thinking skills and literacy abilities regarding the environmental conditions of Bontang City, an industrial city, through Indonesian language learning. The research method employed is a quantitative approach using a pretest-posttest design. The research subjects consist of students enrolled in the Indonesian language course. Data were collected through critical thinking tests, literacy tests, observation, and documentation. The results of the study indicate that Indonesian language learning that integrates local environmental issues is capable of enhancing students’ ability to identify problems, analyse information, evaluate arguments, and formulate logical, data-based solutions. Furthermore, students’ literacy skills also showed an improvement, as demonstrated by